BEEKEEPING IN MOROCCAN RURAL AREAS : VALORIZATION OF A LOCAL PRODUCT THROUGH INTEGRATED FILTER ANALYSIS AND GROUP FOCUS": (CASE OF OUELTANA AMONT, PROVINCE OF AZILAL) - Bakkari Mohamed, El; Abdellatif, Tribak; Anass, Benichou; Bakkari Slimane, El (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2024)
This article delves into the essential role of beekeeping in rural areas of Morocco as a catalyst for economic development and the enhancement of local products. Rooted in local traditions, family beekeeping contributes not only to the diversity of honeys but also to the economic well-being of rural communities. Beekeepers, often united in cooperatives, are committed to a process of valorization, emphasizing quality, certification of origin, and sustainable practices.The approach of this article is distinguished by the use of integrated filter analysis, which explores the multiple facets ofMoroccan beekeeping, from local biodiversity to sustainable practices and from the cultural link to economic prospects.At the same time, group focus is emerging as a powerful investigative tool, allowing rich perspectives to be gathered directly from local actors. This participatory methodology gives a voice to beekeepers, offering an authentic perspective on the challenges and opportunities that punctuate their daily lives.Beyond being a simple economic activity, beekeeping thus becomes a prism through which to explore the deep connection between rural communities and their terrains. This article aims to inspire further reflection on how beekeeping can be optimized, both for the benefit of beekeepers and for the preservation of Morocco's natural wealth.